Liberdades racializadas: gênero, trabalho e crime na fronteira meridional ( Jaguarão, 1870-1905) - Bom, Matheus Batalha (Universidade do Vale do Rio dos Sinos, 2022)
The present study proposes to investigate the meanings of freedom realized by black people in Jaguarão, a city located in the extreme south of Rio Grande do Sul. In this way, we sought to focus attention on the experiences of freedmen and free blacks in the temporal space between 1870 and 1905. The documentary base was formed by inventories, newspapers, manumission letters and, above all, criminal proceedings. We sought to explore as much of the documentation as possible to understand how the legacy of slavery marked the manorial/patronal imagery. On the other hand, it was observed that the black population constructed meanings of freedom autonomous from the process of socio-racial control. Racialization was the guiding principle of the entire work. Through this concept, it was possible to understand the intertwining between themes such as crime, work and gender. Freedom was precarious and racialized, which did not stop black people from constructing authentic meanings in their lives.
Keywords: Liberdade; Racialização; Gênero; Crime; Trabalho; Freedom; Racialization; Gender; Crime; Work; ACCNPQ::Ciências Humanas::História